The effects of ambient air-injection on particulate matter emissions in high firepower chimney cookstoves - Hogberg, Thor, author; Marchese, Anthony, advisor; L'Orange, Christian, committee member; Collett, Jeffrey, committee member; Jathar, Shantanu, committee member (Colorado State University. Libraries, 2017)
Approximately 2.8 billion people use solid fuel to cook and heat their homes. The resulting emissions from using solid fuel to cook and heat has detrimental effects on both indoor and outdoor air quality. In 2012 it was estimated that 4.3 million premature deaths occurred from indoor air pollution and 3.7 million deaths occurred from ambient air pollution. In 2009 it was estimated that incomplete combustion and harvesting of solid biofuels combined accounted for 1.9-2.3% of all greenhouse gases and short lived climate forcers. Due to the high firepower of institutional stoves, they produce far greater amounts of particulate matter (PM) than residential cookstoves; despite this fact, they have received little attention in comparison. Technology at the Advanced Biomass Combustion Laboratory has been developed that is capable of reducing PM emissions in high firepower chimney stoves by over 90%, and shifting the elemental to organic carbon ratio (EC/OC) towards a higher organic fraction. These changes were achieved by the use of high velocity air injection directly above the combustion chamber. Air injection nozzle orifice number, diameter, and the mass flow rate of injection air was tested to understand what combination of geometry and flow rate resulted in the best overall emissions reduction. The most significant emissions reductions occurred at high velocities that resulted from nozzles with fewer and smaller holes.
Keywords: biomass emissions; elemental carbon; particulate matter; cookstoves; aerosol; organic carbon